Inheritance Representation and Right of Transfer - Fernández Arce, César (2005)
This paper analyzes the figures of ius trasmisionis and the right of representation. The latter allows descendants to inherit directly from the deceased, ensuring equitable treatment and following the mandate of the law. On the other hand, the right of transfer involves the transfer of inheritance rights when the original heir does not claim them within the established period. In this case, the person who did not exercise their right to the inheritance ends up passing it on to their own heirs. The text allows us to observe that, although both concepts share similarities in terms of the transmission of inheritance rights to descendants, they differ in the foundations and purposes that sustain them. In short, inheritance representation and the right of transfer are key figures in inheritance law that allow the continuity of succession in specific cases, each with its own characteristics and applications within the corresponding legal framework.